(6)*(3x+2)=(6)*(5x-10)

Simple and best practice solution for (6)*(3x+2)=(6)*(5x-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6)*(3x+2)=(6)*(5x-10) equation:


Simplifying
(6)(3x + 2) = (6)(5x + -10)

Reorder the terms:
6(2 + 3x) = (6)(5x + -10)
(2 * 6 + 3x * 6) = (6)(5x + -10)
(12 + 18x) = (6)(5x + -10)

Reorder the terms:
12 + 18x = 6(-10 + 5x)
12 + 18x = (-10 * 6 + 5x * 6)
12 + 18x = (-60 + 30x)

Solving
12 + 18x = -60 + 30x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30x' to each side of the equation.
12 + 18x + -30x = -60 + 30x + -30x

Combine like terms: 18x + -30x = -12x
12 + -12x = -60 + 30x + -30x

Combine like terms: 30x + -30x = 0
12 + -12x = -60 + 0
12 + -12x = -60

Add '-12' to each side of the equation.
12 + -12 + -12x = -60 + -12

Combine like terms: 12 + -12 = 0
0 + -12x = -60 + -12
-12x = -60 + -12

Combine like terms: -60 + -12 = -72
-12x = -72

Divide each side by '-12'.
x = 6

Simplifying
x = 6

See similar equations:

| R(6x-3)=(4x+7) | | 5n-2(n-2)=-11+3n+5 | | 4y+2=8(y+7) | | 5(-9+x)=-25 | | 6(2+x)=72 | | -2x-30=28-4x | | (3)*(2x+9)=27 | | -8u-30=-6(u+7) | | -3rs(2r^2s+12t-7)= | | -2x-66=62-10x | | 4(x-7)=7x-13 | | K-15=-40 | | -55-2x=-5x+17 | | -5(1+4x)=195 | | 2n+8=3(n-9) | | 3y+18=-6(y-9) | | -31-7x=17-11x | | -3x+5(-9+4x)=-x-4 | | (4)*(3x+12)=64 | | -76+7x=104-2x | | 12x-25=7x+35 | | -4x-14=-7x+12 | | 5x-2(-2x+19)=-83 | | 3(1x+5)=42 | | 8x-68=77+4x | | 3x-6(1+x)=-9x+9 | | 3b-50=4b-74 | | -124+12x=5x+86 | | 9x^2+4x+87=180 | | 6a+70=a | | 8x-151=49-2x | | 5x+3x-9=15 |

Equations solver categories